2007
DOI: 10.1111/j.1365-3040.2007.01733.x
|View full text |Cite
|
Sign up to set email alerts
|

Banksia species (Proteaceae) from severely phosphorus‐impoverished soils exhibit extreme efficiency in the use and re‐mobilization of phosphorus

Abstract: Banksia species (Proteaceae) occur on some of the most phosphorus (P)-impoverished soils in the world. We hypothesized that Banksia spp. maximize P-use efficiency through high photosynthetic P-use efficiency, long leaf lifespan (P residence time), effective P re-mobilization from senescing leaves, and maximizing seed P concentration. Field and glasshouse experiments were conducted to quantify P-use efficiency in nine Banksia species. Leaf P concentrations for all species were extremely low (0.14-0.32 mg P g -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
145
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(160 citation statements)
references
References 52 publications
10
145
1
4
Order By: Relevance
“…This assessment is consistent with the observations by Sulpice et al (2014) and suggests a very high efficiency of the photosynthetic machinery, given that overall leaf area-based rates of photosynthesis in Proteaceae spp. leaves are similar to those of other plants (Denton et al, 2007;Lambers et al, 2012b).…”
Section: Young H Prostrata Leaves Show Delayed Development Of Functisupporting
confidence: 61%
See 4 more Smart Citations
“…This assessment is consistent with the observations by Sulpice et al (2014) and suggests a very high efficiency of the photosynthetic machinery, given that overall leaf area-based rates of photosynthesis in Proteaceae spp. leaves are similar to those of other plants (Denton et al, 2007;Lambers et al, 2012b).…”
Section: Young H Prostrata Leaves Show Delayed Development Of Functisupporting
confidence: 61%
“…prostrata Leaves Senesce Slowly with Early Remobilization of P from RNA Southwestern Australian Proteaceae spp. remobilize scarce nutrients, such as P, very efficiently (Denton et al, 2007), perhaps through a process that extends cell viability (Hörtensteiner and Feller, 2002). Plants grown at the lowest Pi supply in this study showed similar leaf P concentrations compared with plants sampled in the field (Lambers et al, 2012b).…”
Section: Delayed Greening Is Only Partially Reversed By Increased Pi supporting
confidence: 48%
See 3 more Smart Citations